The chesnut handbook : crop & forest management - Beccaro, G. L. (Boca Raton : CRC Press, 2020)
"This book presents techniques in chestnut production. It covers planning and management of chestnut from nursery to orchard production, pest control, and interactions with the environment. It is a valuable resource for agronomists, farmers, researchers, and students of agricultural sciences"--
OCLC-licensed vendor bibliographic record.
Keywords: Chestnut; Chestnut -- Breeding; Chestnut -- Diseases and pests